Analysis Of Credit granting Procedures Guna Bhakti (KGB) and Implamentaation Principle 5C To Minimize Non Performing Loan At Bank BJB - Mayang Lestari; Gatot Wahyu Nugroho; Idang Nurodin (AKUNTANSI 45, 2024)
Banks have an important role in encouraging the economic growth of a country, because most of the Third Party funds are in Commercial Banks. The process of granting credit and applying the 5C principle must be carried out in accordance with Bank policy to avoid non-performing loans. The type of research used by the author is descriptive qualitative method, the data processed are the results of unstructured interviews and observations which will be analyzed qualitatively and described in descriptive form. The procedure for granting Bhakti Guna Credit is in accordance with the Bank's policy at Bank BJB KCP Sukaraja. However, Bank BJB KCP Sukaraja needs to pay attention again regarding credit application procedures and the 5C principle with the established principles because at the time of checking the collateral is still less thorough and there are several factors and obstacles that must be implemented effectively to minimize non-performing loans.